2018
DOI: 10.1002/art.40655
|View full text |Cite
|
Sign up to set email alerts
|

Role of Macrophage Migration Inhibitory Factor in Granulomatosis With Polyangiitis

Abstract: Patients with GPA have an increased frequency of high MIF expression CATT alleles. Higher Mif expression increases the incidence of mortality and pulmonary granulomas in Mif lung-Tg2.1 mice, while anti-MIF treatment protects these mice against death. Blockade of MIF in high genotypic MIF expressers may therefore offer a selective pharmacologic therapy for GPA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…32). The latter mice mimic the approximate 2-fold increase in Mif transcription observed in high MIF expressor genotypes (32). At all DPIs, Mif -/samples contained no measurable MIF, as expected, and Mif-lung-tg BAL contained at least 2-fold more MIF relative to Mif +/+ BAL ( Figure 1A).…”
Section: Iav Infection Promotes Mif Protein Release Into the Airspacesupporting
confidence: 72%
See 1 more Smart Citation
“…32). The latter mice mimic the approximate 2-fold increase in Mif transcription observed in high MIF expressor genotypes (32). At all DPIs, Mif -/samples contained no measurable MIF, as expected, and Mif-lung-tg BAL contained at least 2-fold more MIF relative to Mif +/+ BAL ( Figure 1A).…”
Section: Iav Infection Promotes Mif Protein Release Into the Airspacesupporting
confidence: 72%
“…All animals used for the study were male mice between 2 and 4 months of age and of pure C57BL/6 background. Mif -/and Mif-lung-tg (32,45) mice that were both on a pure C57BL/6 background were used for the study. The Mif-lung-tg mice overexpress Mif in alveolar type II epithelial cells; specifically, these mice had a 0.4-Kb DNA fragment with mouse Mif cDNA inserted into the expression plasmid under control of a CC10 promoter as previously reported (46).…”
Section: Mice and Cell Culturesmentioning
confidence: 99%
“…Gene expression studies indicate that a microsatellite within the MIF promoter (−794 CATT 5-8 , rs5844572) influences MIF expression such that the CATT 5 repeat is a lowexpression allele and the CATT 6 , CATT 7 , and CATT 8 repeats are progressively higher-expression alleles (5,6). Higher CATT repeat number within the MIF promoter also has been linked genetically to susceptibility to or clinical severity of numerous autoimmune inflammatory and infectious disorders (5)(6)(7)(8)(9)(10). The transcription factor inverted CCAAT box-binding protein 90 kd (ICBP90) (also referred to as UHRF1) binds to the MIF promoter microsatellite and is essential for −794 CATT 5-8 length-dependent regulation of MIF transcription (11).…”
Section: Introductionmentioning
confidence: 99%
“…Of note, neutrophils from healthy donors secrete preformed macrophage migration inhibitory factor (MIF) during secondary necrosis, and it is speculated that MIF acts as a danger signal for insufficient clearance of apoptotic neutrophils [ 116 , 117 ]. Interestingly, abnormalities of the MIF gene are more frequent among GPA patients, and using a mouse model, it was demonstrated that overexpression of MIF promotes lung granulomas and increased mortality, thus supporting a role for MIF in GPA [ 118 ]. Apart from neutrophils and monocytes, NG2 + pericytes present around capillaries and arterioles also express MIF [ 31 ].…”
Section: Cells Molecules and Mechanisms Of The Innate Immune Response Fuel The Granulomatous Inflammation In Gpamentioning
confidence: 99%